SURVEY ON CHALLENGES OF ONLINE TEACHING AND LEARNING FOR INTERACTIVE MULTIMEDIA SUBJECT DURING COVID-19 PANDEMIC - Nur Idawati Md Enzai; Mohd Amir Hamzah Ab Ghani; Siti Sara Rais (Journal of Islamic, Social, Economics and Development, 2022)
The unprecedented global pandemic had really impacted all aspects of life including education. Online teaching and learning which used to be the alternative method has been quickly deployed due to schools and universities being closed. As a result, many problems emerged such as technological and emotional well-being issues. This paper addresses the technological issue by conducting a survey among 48 UiTM students enrolled in Diploma Hotel and Tourist Management who take Interactive Multimedia subject. The survey explores the perceptions of students regarding software installation and usage issues. The students’ concerns include difficulty to install software and device does not support the software. The instructor’s view was also obtained and the possible remedies to the challenges are also presented.